2019
DOI: 10.1111/cid.12799
|View full text |Cite
|
Sign up to set email alerts
|

Implant survival rate in calvarial bone grafts: A retrospective clinical study with 10 year follow‐up

Abstract: Background: In this study, we present medium-and long-term data on implant survival in a cohort of patients with severe maxillary atrophy rehabilitated using reconstructive implant site development with calvarial bone grafts. Materials and Methods: We obtained clinical records from patients treated with implant rehabilitation supported by calvaria bone grafts in the Oral Surgery Department of IRCSS San Raffaele (Milan, Italy). Implant and prosthetic survival and success rates were retrospectively evaluated. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
(75 reference statements)
0
34
0
1
Order By: Relevance
“…Several comparative systematic reviews of short implants in combination with vertical ridge augmentation have not found significant differences between short implants and longer implants placed in areas in which vertical bone regeneration procedures were performed, although differences in the number of surgical complications were reported between the two groups, whereby short implants suffered fewer complications. However, it should be noted that most of these studies involved vertical augmentation in the posterior mandible rather than the posterior maxilla, or were case reports, so further research is necessary in order to clarify and compare results between the two treatment options [38][39][40]. In one of the few randomized clinical trials in the literature, Felice et al concluded that the use of 5-mm extra-short implants compared with implants of greater length placed at sites where a bone height regeneration procedure had been performed, produced similar outcomes, whether in the maxilla or mandible [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several comparative systematic reviews of short implants in combination with vertical ridge augmentation have not found significant differences between short implants and longer implants placed in areas in which vertical bone regeneration procedures were performed, although differences in the number of surgical complications were reported between the two groups, whereby short implants suffered fewer complications. However, it should be noted that most of these studies involved vertical augmentation in the posterior mandible rather than the posterior maxilla, or were case reports, so further research is necessary in order to clarify and compare results between the two treatment options [38][39][40]. In one of the few randomized clinical trials in the literature, Felice et al concluded that the use of 5-mm extra-short implants compared with implants of greater length placed at sites where a bone height regeneration procedure had been performed, produced similar outcomes, whether in the maxilla or mandible [41].…”
Section: Discussionmentioning
confidence: 99%
“…In modern dentistry, the use of titanium implants to restore edentulous areas of various extension is a very common practice [1][2][3], followed by a great percentage of long-term success [4]. Systemic or syndromic diseases [5,6] and immune disorders [7] should be evaluated before the implant placement in order to avoid post-operative bleeding-related complications [8,9] and to achieve better outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The task of the dentist and dental hygienist is to monitor the patient so as to avoid progression or any recurrence of these pathologies, restoring a state of health of the tooth support tissues and allowing the success of implant-prosthetic rehabilitations over time [ 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%